LEFTOVER MANAGEMENT COSTS AND WASTE IN CLOTHING MYPES - Bonilla Pastor, Elsie (2015)
Peruvian MYPEs represent 99.3% of all busines-ses with economic initiatives and generate 75% of employment. However, opposite of what happens in developed countries like USA and Japan, their competitiveness is low and the financial condition is fragile, moreover their export share of less than 1%. Inadequate quality management of their processes generates waste and scrap, which increase costs, re-ducing their productivity and profitability. Research conducted on a sample of 27 textile MYPEs-garments manufacturers- located in Lima and Callao, concluded that there is an inverse and significant correlation be-tween the rating of the quality management and the costs of waste and scrap; and found that for every 1% of additional quality management qualification, pro-duction costs are reduced at 0.08 %; we also identified the greatest impact management factors.